KEARIFAN LOKAL MASYARAKAT DALAM PENGELOLAAN KAWASAN HUTAN LINDUNG DI KECAMATAN SENTAJO RAYA KABUPATEN KUANTAN SINGINGI SEBAGAI RANCANGAN MODUL BIOLOGI DI SMA KELAS X - M. Fadillah Fadillah; Suwondo Suwondo; Yuslim Fauziah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: A research has been conducted to find out the community's way of preserving the forest in July-August in Sentajo Raya sub-district of Kuantan Singingi district of Riau Province. The purpose of this research is to understand the local wisdom of the community in the management of Sentajo Raya Forest Protection Area and to analyze the potential of research results As the Design of Biology Module in SMA grade X . This research is carried out in two stages, the data collection stage and the module development stage. The design of the study using survey methods. Determination of samples using snowball sampling technique. The research parameters include planning, utilization, controlling, maintenance, supervision and law enforcement. This study uses primary and secondary data, the data are analyzed descriptively. The module design stage was carried out on the Bina Widya Campus of Riau University by analyzing the research result, potential research results as a source of learning, and design an appropriate learning module for Basic Competence 3.2 Analyze the different levels of biodiversity in Indonesia along with its threats and preservation. the results of the research show that the Sentajo Society has local wisdom in implementing the management of Protected Forest areas, including: Planning, Utilization, Controlling, Maintenance, Monitoring and Law Enforcement. In addition, the community local wisdom in managing Sentajo Raya forest protection area can be used as a design of learning modules on biodiversity conservation material.Keywords: local wisdom, forest management, and module design.